THE EXPRESSION OF CATHEPSIN - D, C- erb B - 2 AND EGFR IN BREAST CANCER AND ITS CORRELATION TO LYMPHATIC METASTASIS - Xu, Liangzhong; Zhu, Weiping; Zhang, Taiming; Jing, Aiping; Shen, Zhenzhou (Chinese Journal of Cancer Research, 2013)
The expression of Cathepsin - D (Cath - D), c - erbB - 2 and EGFR in breast cancer and its correlation to lymphatic metastases were studied in 277 cases by imnnmohistochemical technique. Positive staining of Cath- D was detected in 107 cases (38.62%). Among those, 89 cases (83.17%)had docmnented metastases in the lymph nodes. One hundred and seventy cases ( 61.38% ) stained negative for Cath - D. Of which 64 cases (37.64 % ) had detectable lymphatic metastases. There is a significant difference in the rate of the lymphatic metastases between the Cath- D positive and Cath - D negative groups ( x2 = 55.05 P < 0.0001). Fifty-six out of 107 Cath- D positive cases (52.23%) were c-erbB-2 positive as well. However, only 27 out of 170 Cath- D negative cases (15.88%) wene e-erbB-2 positive. The positive rate of c-erbB-2 in Cath - D positive group was significantly different from that of Cath - D negative group ( x2 = 41.58 P